The Significance of Innovation Orientation in Firm Performance: Technological Capabilities as a Moderating Role - Fegada, Alfateh; Veres, Zoltan (European Scientific Journal, ESJ, 2024)
Entrepreneurial marketing â€œEMâ€ is considered to be suitable for small businesses. However, innovation orientation â€œIOâ€ as an EM dimension is a critical instrument that small and medium-sized businesses can use to obtain a competitive advantage. Thus, the general objective of this study is to explore and describe the significant relationship between IO and firm performance â€œFPâ€ in SMEs in Khartoum-Sudan utilizing technological capabilities â€œTCPsâ€ as a moderating variable. The resource-based view â€œRBVâ€ provides the theoretical foundation for this study regarding the effect of innovation orientation on firm performance through technological capabilities. To achieve this objective, we assumed the following hypothesis: H1: Innovation orientation has a significant relationship with firm performance profitability, sustainability, and customer satisfaction. H2: We assume that TCPs can positively moderate the relationship between IO and FP. In this manner, our study is quantitative. Reliable with the purpose of this study. Furthermore, our study relied on the â€œPositivism philosophyâ€, a deductive approach to theory development. Accordingly, overall, 255 responses were received in responding to our online questionnaire. To analyze the data firstly PCA, Correlation, and Rotation matrix were utilized to test the appropriateness of the study pre-model and check the validity of the questionnaire measurements. secondly, we used Path analysis to examine the significant relationships between study variables. Consequently, the findings confirm both significant and insignificant relationships between IO and FP. Our analysis revealed significant relationships between innovation orientation, technological capabilities, and firm performance indicators such as profitability, sustainability, and customer satisfaction. Moreover, we found that technological capabilities play a crucial moderating role in enhancing the effects of innovation orientation strategy on firm performance. Anyhow, these results confirmed the partial support of the studyâ€™s hypotheses.